2003
DOI: 10.1046/j.1440-1746.2003.03015.x
|View full text |Cite
|
Sign up to set email alerts
|

Randomized controlled trial to compare the dose of adjuvant chemotherapy after curative resection of hepatocellular carcinoma

Abstract: There is no significant difference in the survival rates between the two groups. Adjuvant chemotherapy may not be useful.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2005
2005
2013
2013

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 15 publications
1
14
0
Order By: Relevance
“…Tumor dormancy, observed clinically, is generally thought to reflect the existence of residual tumor cells that fail to respond to a conventional treatment regimen (15)(16)(17)(18). Residual tumor cells may be kept in check by various mechanisms, including the host immune system, tumor cell microenvironment, and/or angiogenic or autocrine growth factor capability (19)(20)(21)(22)(23).…”
Section: Tumor Dormancy and Cancer Stem Cellsmentioning
confidence: 99%
See 1 more Smart Citation
“…Tumor dormancy, observed clinically, is generally thought to reflect the existence of residual tumor cells that fail to respond to a conventional treatment regimen (15)(16)(17)(18). Residual tumor cells may be kept in check by various mechanisms, including the host immune system, tumor cell microenvironment, and/or angiogenic or autocrine growth factor capability (19)(20)(21)(22)(23).…”
Section: Tumor Dormancy and Cancer Stem Cellsmentioning
confidence: 99%
“…Treatment of many types of cancers, including breast cancer, lymphoma, leukemia, and sarcomas, can be associated with long-term regression of tumors, only to be followed by relapse at a much later time (15)(16)(17)(18). The specific type of cancer can often predict the outcome of treatment.…”
Section: Clinical and Therapeutic Implications Of Tumor Dormancymentioning
confidence: 99%
“…In another study, postoperative intra-arterial injection of iodine131 labeled lipiodol (131I-Lip) was found to decrease the HCC recurrence rate in patients after hepatectomy, improving the 1-, 2-, and 3-year survival rates when compared with the survival rates in the control group receiving no 131I-Lip treatment [34] . The adjuvant chemotherapy was not effective in preventing the postoperative recurrence [35] . The mechanisms of the anticancer effect of P 32 -GMS have been discussed.…”
Section: Discussionmentioning
confidence: 93%
“…In a recent prospective randomized controlled trial, Kwok et al demonstrated that the positive benefits of using TACE as an adjuvant treatment are unclear. 7 In contrast, Ren et al demonstrated that postoperative adjuvant TACE can prolong the survival of patients with risk factors for residual tumour, but could not prolong the survival of patients without risk factors for residual tumour. 8 In a recent meta-analysis the authors suggested that the use of postoperative transarterial chemotherapy with or without embolization may improve survival.…”
Section: Discussionmentioning
confidence: 96%